Isolating the impact of COVID-19 lockdown measures on urban air quality in Canada - Rabab Mashayekhi; Radenko Pavlovic; Jacinthe Racine; Michael D. Moran; Patrick M. Manseau; Annie Duhamel; Ali Katal; Jessica Miville; David Niemi; Si Jun Peng; Mourad Sassi; Debora Griffin; et al. (Air Quality, Atmosphere & Health, 2021)
We have investigated the impact of reduced emissions due to COVID-19 lockdown measures in spring 2020 on air quality in Canada’s four largest cities: Toronto, Montreal, Vancouver, and Calgary. Observed daily concentrations of NO 2 , PM 2.5 , and O 3 during a “pre-lockdown” period (15 February–14 March 2020) and a “lockdown” period (22 March–2 May 2020), when lockdown measures were in full force everywhere in Canada, were compared to the same periods in the previous decade (2010–2019). Higher-than-usual seasonal declines in mean daily NO 2 were observed for the pre-lockdown to lockdown periods in 2020. For PM 2.5 , Montreal was the only city with a higher-than-usual seasonal decline, whereas for O 3 all four cities remained within the previous decadal range. In order to isolate the impact of lockdown-related emission changes from other factors such as seasonal changes in meteorology and emissions and meteorological variability, two emission scenarios were performed with the GEM-MACH air quality model. The first was a Business-As-Usual (BAU) scenario with baseline emissions and the second was a more realistic simulation with estimated COVID-19 lockdown emissions. NO 2 surface concentrations for the COVID-19 emission scenario decreased by 31 to 34% on average relative to the BAU scenario in the four metropolitan areas. Lower decreases ranging from 6 to 17% were predicted for PM 2.5 . O 3 surface concentrations, on the other hand, showed increases up to a maximum of 21% close to city centers versus slight decreases over the suburbs, but O x (odd oxygen), like NO 2 and PM 2.5 , decreased as expected over these cities.